Potential of circulating lncRNA CASC2 as a biomarker in reflecting the inflammatory cytokines, multi‐organ dysfunction, disease severity, and mortality in sepsis patients. Issue 8 (26th June 2022) - Wang, Rui; Zhao, Jinglin; Wei, Qi; Wang, Hao; Zhao, Chao; Hu, Caihong; Han, Yu; Hui, Zhi; Yang, Long; Dai, Qingchun; Liu, Cuicui
Abstract: Background: Long noncoding RNA (lncRNA) cancer susceptibility candidate gene 2 (CASC2) inhibits inflammation and multi‐organ dysfunction in various ways. The present study was intended to explore the potency of blood lncRNA CASC2 as a biomarker for sepsis management. Methods: Totally, 184 sepsis patients and 30 healthy controls were enrolled. The reverse transcription‐quantitative polymerase chain reaction was used to detect lncRNA CASC2 expression in peripheral blood mononuclear cell samples from the subjects. Mortality during 28 days was recorded in sepsis patients. Results: LncRNA CASC2 was decreased in sepsis patients [median (interquartile range [IQR]): 0.473 (0.241–0.773)] by comparison to healthy controls [median (IQR): 1.019 (0.676–1.685)] ( p  < 0.001). In sepsis patients, lncRNA CASC2 was negatively correlated with Acute Physiology and Chronic Health Evaluation II (APACHE II) ( p  = 0.001), Sequential Organ Failure Assessment (SOFA) ( p  < 0.001), SOFA‐respiratory system ( p  = 0.010), SOFA‐coagulation ( p  = 0.020), SOFA‐liver ( p  = 0.019), and SOFA‐renal ( p  = 0.010) scores, but was not related to SOFA‐nervous ( p  = 0.466) and SOFA‐cardio vascular system ( p  = 0.059) scores. Additionally, lncRNA CASC2 was negatively related to tumor necrosis factor‐α ( p  = 0.024), interleukin (IL)‐1β ( p  = 0.013), and IL‐17A ( p  = 0.002), but was not linked to IL‐6 ( p  = 0.112) or IL‐10 ( p  = 0.074). Furthermore, lncRNA CASC2 was lower in sepsis deaths [median (IQR): 0.286 (0.166–0.475)] than in survivors [median (IQR): 0.534 (0.296–0.811)] ( p  < 0.001). Simultaneously, Kaplan–Meier (KM) curve analysis also observed that lncRNA CASC2 was inversely related to accumulating mortality in sepsis patients ( p  = 0.003). While lncRNA CASC2 could independently predict lower mortality risk. Conclusion: Circulating lncRNA CASC2 inadequacy indicates the release of inflammatory cytokines, severe multi‐organ injuries, and increased mortality in sepsis patients. Abstract : Figure 1. LncRNA CASC2 was reduced in sepsis patients compared to healthy controls. LncRNA CASC2 in sepsis patients and healthy controls (A); ROC curve of lncRNA CASC2 in distinguishing sepsis patients from healthy controls (B); different sensitivity and specificity when lncRNA CASC2 at 1/4 quartile, median, and 3/4 quartile in sepsis patients was set as the cut‐off value (C).